ALGORITHM FOR DETECTION OF ABUSIVE CONTENT IN AUDIO CONTENT FOR IMPLEMENTATION IN OBJECT-ORIENTED INFORMATION SYSTEM - MOLCHANOVA, MARYNA; MAZURETS, OLEKSANDR; SOBKO, OLENA; VIT, ROMAN; NAZAROV, VIACHESLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper proposes the basic principles of developing an object-oriented information system for detecting abusive content in Ukrainian-language audio content based on a new algorithm that uses statistical and neural network approaches to detect abusive content. Detecting offensive content in text and audio content is an urgent task, as it helps to create a safe and healthy environment for communication, especially in online platforms. Offensive content can harm the people who hear or read it and violate their rights. It can also have a negative impact on society, contributing to the spread of hatred and violence.To detect abusive speech in audio content, the proposed approach uses two key components: the use of dictionary methods and the analysis of the emotional tonality of utterances. A set of reviews was used as a dataset to determine the abusive component of the content, which was expanded by the authors by adding words of abuse.An object-oriented information system architecture written in the Python programming language in the PyCharm programming environment is proposed. The information system consists of a software module for training recurrent neural network models and further saving trained instances, and a software module for detecting abusive content in Ukrainian-language audio content using trained RNN models. Since the recurrent neural network is trained on a short text data set, the system is less efficient at identifying texts that have a larger number of words. In the example of the proposed approach, the accuracy of detecting offensive content is more than 90%. This means that the algorithm works correctly in the absence of offending highlights in the test data set. The results of the analysis of the effectiveness of the proposed approach show that in the vast majority of cases the conclusions regarding the acceptability of audio content based on the level of abuse are correct.
Keywords: abusive content detection; RNN; audio content; object-oriented approach